Mechanistic insights into the influences of photovoltaic panel construction on algal crust microbial communities in alpine desert grasslands - Qi, Desheng; Zhao, Xin; Zhang, Ni; Yang, Ziwei; Chen, Yarong; Chen, Kelong (Frontiers in Environmental Science, 2025)
Photovoltaic (PV) park construction has a profound impact on the regional microclimate and ecosystem carbon cycle. Meanwhile, biological soil crusts (BSCs) also play a crucial role in the carbon and nitrogen cycles of desert ecosystems. However, the response mechanism of algal BSC microbial communities to PV panel construction is still poorly elucidated. In this study, high-throughput sequencing was utilized to explore the mechanism underlying the effects of PV panel construction on algal BSC microbial communities in the Talatan PV Base. The results showed that the predominant bacterial phyla of algal BSCs in desert grassland were Actinobacteriota and Proteobacteria. PV panel construction changed the structure of algal BSC bacterial communities, which significantly increased the relative abundance of Proteobacteria and enhanced the interconnectivity between bacterial species. Nevertheless, the response of bacterial community diversity to the construction of PV panels was not significant (P > 0.05). PV panel construction altered the microenvironment by significantly increasing temperatures under the panels while significantly reducing soil carbon stocks. In addition, temperature and carbon content were the most important factors influencing the structure and diversity of algal BSC bacterial communities in alpine desert grasslands. In summary, the installation of photovoltaic panels led to a notable elevation in the temperature underneath them. This temperature increase, in turn, enhanced the stability of the bacterial communities within the algal BSC in alpine desert grasslands. Simultaneously, it significantly reduced the carbon storage capacity in these grasslands, thus exerting a dual-edged impact on the ecological environment of the region.